Performance analysis of kisan credit card scheme in Thiruvananthapuram district - Kshama A V (Department of Agricultural Economics, College of Agriculture, 2018)
The research entitled ‘Performance analysis of Kisan Credit Card in Thiruvananathapuram district’ was conducted with the objectives of examining the progress and performance of Kisan Credit Card at macro and micro level and to identify the constraints faced by beneficiaries. The secondary data were collected regarding the number of cards issued and the amount sanctioned at all India level and Kerala state level from various government institutions and banking publications for a period of 10 years. Primary data were collected from Parassala panchayat of Neyyattinkara taluk. The information was collected from 30 KCC beneficiaries and 30 non-beneficiaries randomly selected from the major commercial and co-operative banks of the locality. Thus the total sample size was 60. For the number of cards issued, Kerala recorded a lower Compound Annual Growth Rate (CAGR) than all India which was 3.03 and 13.74 per cent per annum respectively. Whereas for the amount sanctioned the performance of Kerala state was better (22 per cent per annum) compared to all India (18 per cent per annum). The amount per card sanctioned by the banking sector showed a growth rate at of 19 per cent and 4 per cent per annum for Kerala and India state respectively which indicates a tendency of credit deepening in Kerala rather than credit widening. Binary logit regression was done to know the socio economic variables influencing the respondents of the scheme. Analysis showed that cropping pattern and eductaion of the respondents were found to have positive influence indicating, a respondent who is following a particular cropping pattern is 1.3 times more likely to join KCC when compared to the once who are not following any cropping pattern. Similarly in case of education, education the odds ratio was found to be 1.61 indicating that as the education level of the respondents increases then they are 1.61 times more likely to join the scheme rather than the respondents who have not done any formal schooling. The total cost of cultivation was estimated using ABC Cost concept, considering both fixed and variable costs. The most profitable crop was banana, followed by yard long bean, cucumber, tapioca and amaranthus and the B:C ratios were 1.10, 1.06, 1.03, 1.03 and 1.02 respectively at Cost C. From the results of regression analysis it was evident that the coefficient of determination had values ranging from 0.68-0.80 indicating 68-80 per cent of the variation in the gross returns was due to the independent variables under consideration. It was found that 50 per cent of the respondents joined the scheme during 2009-13 and 40 per cent joined during 2006-09. About 50 per cent of respondents obtained information from Krishi Bhavan followed by 33 per cent from banks as a source and 13 per cent from Horticorp. The average amount applied for the loan was ₹60,666.66 and it was more in case of beneficiaries of SBI (₹69,333) than co-operative bank (₹52,000). The average number of renewal of the accounts was found to be 5.73 times. While considering repayment, 73 and 86 per cent of the beneficiaries of SBI and Co-operatives respectively were able to repay the loan amount completely. The average amount of loan sanctioned was more for beneficiaries of SBI but the repayment was better for the loanees of co-operative bank. Scale of finance was compared with Cost A2 and Cost C for the various crops. Invariably for all crops the credit was adequate while considering paid out costs (Cost A2). At Cost C, credit was found adequate for all crops except tapioca. The total cost of credit was found to be higher for beneficiaries of Co-operative bank (7.4 per cent) compared to beneficiaries of SBI (7.2 per cent). It was evident from the ordinary least square estimates that cost of cultivation and loan requirement for non-farming operations were influencing the credit requirement of the respondents positively. The major constraints as perceived by the beneficiaries were with respect to procedural formalities which include time delay and formalities for obtaining the land records from village office and multiple visits to the bank for the sanction. Moreover the credit limit under the scheme was not considering the consumption needs and also respondents found difficulty in annual renewal of the KCC account. The amount per card issued in Kerala state was low when compared to all India level eventhough the growth rate was more which warrants for expansion of credit for agricultural development. The beneficiaries of KCC were able to purchase better quantity and quality of inputs thereby leading to higher profitability from various crops. The inputs were found to be over utilized, which shows that the respondents can increase their income by rational use of inputs. In the opinion of respondents, the consumption needs are more prominent than production credit and if family size is considered as criteria for fixing consumption credit limit the KCC scheme would be more attractive. The linking of KCC with storage and warehousing facility and marketing agencies would avoid indebtedness of farming community.